Time-dependent dual effects of high levels of unconjugated bilirubin on the human blood-brain barrier lining - Palmela, Inês; Sasaki, Hiroyuki; Cardoso, Filipa L.; Kim, Kwang S.; Brites, Dora; Brito, Maria A. (Frontiers in Cellular Neuroscience, 2012)
In neonatal jaundice, high levels of unconjugated bilirubin (UCB) may induce neurological dysfunction (BIND). Recently, it was observed that UCB induces alterations on brain microvasculature, which may facilitate its entrance into the brain, but little is known about the steps involved. To evaluate if UCB damages the integrity of human brain microvascular endothelial cells (HBMEC), we used 50 or 100 μM UCB plus human serum albumin, to mimic the neuropathological conditions where levels of UCB free species correspond to moderate and severe neonatal jaundice, respectively. Our results point to a biphasic response of HBMEC to UCB depending on time of exposure. The early response includes increased number of caveolae and caveolin-1 expression, as well as upregulation of vascular endothelial growth factor (VEGF) and its receptor, VEGFR-2. In contrast, later effects are the reduction in zonula occludens-1 and β-catenin levels and thus of TJ strands and cell-to-cell contacts. In addition, reduction of the transendothelial electrical resistance and increased paracellular permeability are observed. The 72 h of HBMEC exposure to UCB triggers a cell response to the stressful stimulus evidenced by increased autophagy. In this later condition, the UCB intracellular content and the detachment of both viable and non-viable cells are increased. Taken together, these results indicate biphasic effects of UCB on HBMEC lining depending on the time of interaction. In the early phase, changes in caveolin-1 and VEGFR-2 are produced without alterations on the paracellular permeability. In opposite, irreversible damage of UCB to HBMEC, with the loss of the barrier properties and cell detachment together with autophagy predominate in the later phases of injury. These findings contribute to understand why the duration of hyperbilirubinemia is considered one of the risk factors. Indeed, facilitated brain entrance of the free UCB species will favor its parenchymal accumulation and BIND.